Hill`s equation in the arm push of shot put - Rahikainen, A.; Virmavirta, M.; Ranta, M. A. (Current Journal of Applied Science and Technology, 2016)
Aims: The purpose of this paper was to continue the previous study of arm rotation movement where A.V. Hill`s force-velocity relationship was transformed into a constant maximum power model consisting of three different components of power.